Screening the Global Health Priority Box against Plasmodium berghei liver stage parasites using an inexpensive luciferase detection protocol - Gia-Bao Nguyen; Caitlin A. Cooper; Olivia McWhorter; Ritu Sharma; Anne Elliot; Anthony Ruberto; Rafael Freitas; Ashutosh K. Pathak; Dennis E. Kyle; Steven P. Maher (Malaria Journal)
Abstract Background Malaria, a disease caused by parasites of the genus Plasmodium, continues to impact many regions globally. The rise in resistance to artemisinin-based anti-malarial drugs highlights the need for new treatments. Ideally, new anti-malarials will kill the asymptomatic liver stages as well as the symptomatic blood stages. While blood stage screening assays are routine and efficient, liver stage screening assays are more complex and costly. To decrease the cost of liver stage screening, a previously reported luciferase detection protocol requiring only common laboratory reagents was adapted for testing against luciferase-expressing Plasmodium berghei liver stage parasites. Methods After optimizing cell lysis conditions, the concentration of reagents, and the density of host hepatocytes (HepG2), the protocol was validated with 28 legacy anti-malarials to show this simple protocol produces a stable signal useful for obtaining quality small molecule potency data similar to that obtained from a high content imaging endpoint. The protocol was then used to screen the Global Health Priority Box (GHPB) and confirm the potency of hits in dose–response assays. Selectivity was determined using a galactose-based, 72 h HepG2 assay to avoid missing mitochondrial-toxic compounds due to the Crabtree effect. Receiver-operator characteristic plots were used to retroactively characterize the screens’ predictive value. Results Optimal luciferase signal was achieved using a lower HepG2 seed density (5 × 103 cells/well of a 384-well microtitre plate) compared to many previously reported luciferase-based screens. While producing lower signal compared to a commercial alternative, this luciferase detection method was found much more stable, with a > 3 h half-life, and robust enough for producing dose–response plots with as few as 500 sporozoites/well. A screen of the GHPB resulted in 9 hits with selective activity against P. berghei liver schizonts, including MMV674132 which exhibited 30.2 nM potency. Retrospective analyses show excellent predictive value for both anti-malarial activity and cytotoxicity. Conclusions This method is suitable for high-throughput screening at a cost nearly 20-fold less than using commercial luciferase detection kits, thereby enabling larger liver stage anti-malarial screens and hit optimization make-test cycles. Further optimization of the hits detected using this protocol is ongoing.